The Capital Structure Puzzle in China - Zhang, Yujie (2009)
This paper concentrates on one of the most famous puzzle in corporate financing, the capital structure puzzle in developing countries. While in western countries the theoretical and empirical underpinnings of capital structure have a great progress in recent decades, they are still ambiguous and controversial in developing countries. To fill the gap of empirical researches in developing countries, in this study, the sample from Chinese-listed firms are collected for testing this puzzle. It is worth to mention that the data and methodology in our paper are critically justified in order to make sure our empirical results are reliable. We tend to figure out this capital structure puzzle by looking into these aspects. First of all, by implying western capital structure model to our Chinese sample, it is find out the western model has a limited applicability to Chinese-listed firms. In other word, the theoretical underpinning behind this western experienced model has a limited explanatory power to the financing behavior of the Chinese corporations. Moreover, by looking more specifically, the relationships between dependent variable (gearing ratio) and each independent variables (determinants) are not all consistent with their experiences in western countries. Growth opportunity and firm size, for example, reject the hypotheses based on western empirical researches. Although profitability and tangibility show the same results with our hypotheses, the explanations for western countries, to a large extent, are not workable for Chinese firms. Therefore, we argue that the influential factors for the financing decision in Chinese corporations are derived from the country‘s unique institutional environment and corporate governance structure, rather than the theories derived form western settings. To further prove our conclusions, we conduct robust test to our new model, which include two additional variables, state ownership and institutional ownership. Importantly, the two variables increase the explanatory power of the model significantly, and thus, again prove that the unique institutional environment and concentrated corporate ownerships are influential to the capital structure of Chinese-listed firms.